Serum concentrations of per- and poly-fluoroalkyl substances (PFAS) in Danish pregnant women—temporal trends during pregnancy, correlations with partners, associations with physical activity, and blood lipid concentrations - Ida Karoline Bach Jensen; Esben Budtz-Jørgensen; Christian Lindh; Caroline Borup Roland; Signe de Place Knudsen; Jane M. Bendix; Stig Molsted; Tine D. Clausen; Bente Stallknecht; Ole H. Mortensen; Ellen Løkkegaard; Lisbeth E. Knudsen (Environmental Health)
Abstract Background Per- and polyflouralkyl substances (PFAS) are a group of persistent chemicals used extensively in industries and consumer products due to their water-repellent properties. Studies have linked PFAS exposure to adverse health effects, and human exposure to PFAS, especially during pregnancy, is of great concern. In this study, we report how serum PFAS concentrations during pregnancy correlated with serum PFAS of partners from the same household. Further, we report how serum PFAS concentrations change during the course of pregnancy and associations between PFAS and blood lipid concentrations as well as exploratory analyses of associations between physical activity and PFAS concentrations. Methods In this secondary analysis of data from the FitMum study conducted from 2018 to 2021, 216 healthy, pregnant women, and 110 of their partners were included. Non-fasting venous blood samples were collected from the mothers at three test visits during pregnancy and at delivery, where blood from partners were also collected. Serum samples from all timepoints were analyzed for 15 short- and long-chained PFAS using liquid chromatography triple quadrupole linear ion trap mass spectrometry. Total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) and triglyceride blood concentrations were measured at three test visits during pregnancy and at delivery. Physical activity was measured with a wrist-worn activity tracker 24/7 from inclusion before gestational age week 15 + 0 and throughout pregnancy. Results In serum samples we detected the following PFAS: PFOS, PFOA, PFHxS, PFNA, PFDA, and PFUnDA. The maternal median concentrations at baseline were: PFOS: 4.09 ng/mL, PFOA: 0.81 ng/mL, PFHxS: 0.29 ng/mL, PFNA: 0.42 ng/mL, PFDA: 0.25 ng/mL, and PFUnDA: 0.19 ng/mL. Partner serum PFAS concentrations were 3–145% higher than maternal concentration (except for PFUnDA). PFAS concentrations correlated within couples. All PFAS decreased significantly during pregnancy (PFOS -23.1 percent 95%-CI [-31.9;-13.2] from baseline to delivery). All PFAS concentrations were associated with increased HDL-C concentrations. No associations between physical activity and maternal PFAS concentrations were found. Conclusions Overall, serum PFAS concentrations decreased during pregnancy. PFAS concentrations within households were strongly correlated. PFAS and HDL-C concentrations were positively associated. We found no associations between physical activity and serum PFAS concentrations. Trial registration The study was registered at ClinicalTrials.gov; NCT03679130; 20/09/2018.